Business Training and Mentoring : Experimental Evidence from Women-Owned Microenterprises in Ethiopia - Bakhtiar, M. Mehrab; Bastian, Gautam; Goldstein, Markus (World Bank, Washington, DC, 2021)
Recent research shows that microenterprises in developing countries are constrained by their managerial capacity, especially in the areas of marketing, record keeping, financial planning, and stock control. In a stratified randomized controlled trial, experienced businesswomen in Ethiopia were given a formal business training that addressed these constraints. A second-stage mentoring component in which a random selection of female mentees within the social and business network of the trainees from the first-stage business training received customized mentoring from these “trained mentors.” Pooled results using three rounds of post-training surveys carried out over three years show that business training causes profit and sales to improve by 0.21 standard deviation, while business practices improve by 0.13 standard deviation. The overall impact of mentoring is muted—strong impacts are observed on the adoption of business practices among mentees, but there is no statistically significant impact on profits.